Pedagogização emocional e desempenho na escola - Hennemann, Maurício Marks (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation aims to understand and discuss how the emotional discourses in evidence in school digital media are presented and related to the excellence recognized by Enem. To this end, the content circulating in the digital media of the ten best-placed schools in the 2019 Enem ranking was analyzed. The first analytical movement carried out was mobilized by questioning how such schools enunciate themselves in their digital media, where it was observed that an emotional content in the publications stand out, mainly observed on Facebook and Instagram, social networks that show greater engagement and number of followers. The second analytical movement into the materials made it possible to observe the instrumentalization of emotional issues aimed at performance and productivity within the schools, thus allowing one to think about today’s school inserted in the intricacies of an emotional capitalism, in which economic and emotional discourses mix up and shape one another. It was concluded, then, that the emotional discourses in evidence in the digital media of schools considered of excellence, according to the parameters of Enem, are manifested through individual practices and practices external to the individual, evidencing a kind of emotional pedagogization which purposes refer to emotional preparation of students, bearing in mind the demands of school performance in different evalutions and competitions, in a neoliberal political and educational scenario in which the State assumes the role of an evaluator instead of an executing State.
Keywords: Desempenho; Avaliação de larga escala; Enem; Capitalismo emocional; Pedagogização emocional; Performance; Large scale evaluation; Emotional capitalism; Emotional pedagogization; ACCNPQ::Ciências Humanas::Educação